Perancangan Mesin Pengupas Buah Pinang Berbasiskan Metode Quality Function Deployment (Qfd) - Angga Pranata; Yohanes Yohanes; Satriardi Satriardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Areca peeler machine design is one of the processes to increase productivity. Areca stripping process is generally done manually, ie by spliting and dried until the Areca is actually already dry. Areca peeler machine design is intended to facilitate farmers in processing agricultural products Areca so as to increase production capacity and benefits also increased. Areca peeler machine design using quality function deployment method that aims to get the design that corresponded to the wishes of the community. Customer voice and customer need is obtained from the results of questionnaires. Areca stripping mechanism that is by grinding the areca husks as a result of the round blade, assisted by feeding screw as a conductor of the fruit. Dimensions of Areca peeling machine obtained from anthropometry Indonesia.Keyword : areca, machine parer areca, Quality Function Deployment Method, anthropometric Indonesia